Tinjauan Hukum Islam Terhadap Pelaksaan Distribusi Zakat Pada BMT Amanah Ummah Kartasura Tahun 2014 - Assiba'i, Muhammad Husni, Dr. Imron Rosyadi, M.Ag (2016)
Baitul Māl wat Tamwīl (BMT) Amanah Ummah is the Islamic financial institutions that have special concern for the economic empowerment of the people. Baitul Māl Amanah Ummah is a part of the BMT AmanahUmmah moving to service management and distribution of zakat, donation, shodaqoh and endowments (ZISWAF). This study aims to find out who are the recipients of BMT AmanahUmmah in 2014 as well as to find out any other kind of distribution of zakat in BMT AmanahUmmah in 2014 given to the community. This study is a qualitative study using a descriptive approach. Data obtained from the documents BMT, and interviews with the management of the Baitul Māl BMTAmanahUmmah Kartasura. Data analysis using a portrait of evaluative analysis of the implementation of the distribution of zakat in BMT AmanahUmmah than give a judgment according to Islamic law. The results have showed the distribution zakat being not agree with Islamic law because the distribution of zakat is just for 4 (four) aṣnāf of 8 (eight) aṣnāf there. According to the author, in distribution to needy people there are who should not receive zakat as members of the poor classes because the distribution is given in collaboration with Aisyiyah Islamic learning groups. While on 'āmil group and sabīlillāh BMT AmanahUmmah is in conformity with the Islamic laws. In zakat distribution to the public, BMT AmanahUmmah still distributes both consumptive and consumptive traditional or creative provision of food packages and scholarships to ḍu'afā' having achievement or the other, while the distribution of the productive provision is still so less.